Climatic Influences in the Management of Poplar Leaf Rust - Chandrashekar, M. (Indian Forester, 1983)
The resistance expressed by a number of cultivars of poplar to Melampsora leaf rusts is differentially sensitive to the temperature and light intensity. Such a response has been suggested to reinforce diversity in the populations of the pathogen and cause stability in the resistance of the host. The implications of these results to the natural ecosystem and in the management of the poplar groves are discussed.